A Study of Oguchi Approximation (OA) for Ising-Spin Magnetic Model - Abbass, Raied (University of Thi-Qar Journal of Science, 2008)
An isospin magnetic system with spin values S=1 is studied for square and simple cubic lattice, the curie temperature has been calculated for these lattices based on the usual Oguchi approximation (OA).Within this scheme considered here, four atoms are considered where the three nearest-neighbor spin correlation are taken into account when the Hamiltonian is derived. The results for the critical temperature are remarkably accurate comparing to the effective field ones.